Assessment of level of knowledge and satisfaction of website about cleft lip and palate - Picinato-Pirola, Melissa; Magalhães, Raíssa Gomes; Ribeiro, Marilia Gabriela Gonçalves; Seles, Thiago Pestillo [UNESP]; de Castro Corrêa, Camila (FapUNIFESP (SciELO), 2025)
Purpose: To promote orientation about cleft lip and palate and to verify knowledge and satisfaction of an orientation program through a website developed for students and health professionals. Methods: This is a cross-sectional study, 13 healthcare professionals and 81 students from the areas of nursing, speech-language pathologist, medicine, nutrition, dentistry, and psychology participated. The research consisted of three stages: filling out a pre-program questionnaire, accessing the website (http://fissuralabiopalatina.unb.br/) developed by the researchers and filling out a post-program questionnaire. For the statistical analyses McNemar’s, Chi-square and Fisher’s Exact Tests were used. Results: The majority of students were enrolled in the eighth semester of graduation or above, with little or no prior contact with the CLP. After accessing the website, there was an increase in knowledge for eight questions (p≤0.05). 70.2% consider their satisfaction when accessing the website to be excellent, 24.5% very good and 5.3% good. 44.7% of participants praised the website’s design and layout, accessible language and informative content. Conclusion: It was possible to promote the guidelines about cleft lip and palate on the website, observing was an expansion of the topic for students and health professionals.
Keywords: Cleft Lip; Cleft Palate; Computer Communication Networks; Health Promotion; Interdisciplinary Communication